2018
DOI: 10.1039/c7rp00233e
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry and industry inspired laboratories: the impact on students’ perceptions of skill development and engagements

Abstract: Many examples exist in the chemical education literature of individual experiments, whole courses or even entire year levels that have been completely renewed under the tenets of context-based, inquiry-based or problem-based learning. The benefits of these changes are well documented and include higher student engagement, broader skill development and better perceived preparation for the workforce. However, no examples appear to have been reported in which an entire school's teaching laboratory programme has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
2
24
0
1
Order By: Relevance
“…Students may undergo different learning experiences and attain various learning outcomes even though they are provided with the same material, have the same instructor, and learn the same content in the same classroom, (George-Williams, et al, 2018;Kousa, et al, 2018). This finding suggests that students' learning may therefore depend upon their interactions during the laboratory activity; this hypothesis is at the core of the present study.…”
Section: Nature Of Interactions In Science Laboratoriesmentioning
confidence: 77%
See 1 more Smart Citation
“…Students may undergo different learning experiences and attain various learning outcomes even though they are provided with the same material, have the same instructor, and learn the same content in the same classroom, (George-Williams, et al, 2018;Kousa, et al, 2018). This finding suggests that students' learning may therefore depend upon their interactions during the laboratory activity; this hypothesis is at the core of the present study.…”
Section: Nature Of Interactions In Science Laboratoriesmentioning
confidence: 77%
“…In response to the call for an increased amount of research in laboratory settings, several studies have explored students' perceptions and their intended goals in traditional or reformed undergraduate laboratories (DeKorver and Towns, 2015;Galloway and Bretz, 2015a;Galloway and Bretz, 2015b;Chopra, et al, 2017;George-Williams, et al, 2018). Other studies have developed structured observation instruments to improve instructional practices (Lund, et al, 2015;Velasco, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The application of inquiry-based laboratory in university science classes is increasing. In recent years, with the science teachers becoming more and more critical of the effectiveness of the cookbook type laboratory activities and the purpose, practice and learning performance of the laboratory, people's interest in using inquiry teaching strategies is on the rise (Haglund, Melander, Weiszflog, & Andersson, 2017;George-Williams, Soo, Ziebell, Thompson, & Overton, 2018;Wheeler, Chiu, Maeng, & Bell, 2019). Lord & Orkwiszewski (2006) indicated that inquiry based laboratory activities is an effective way of learning, which can enhance students' content learning knowledge, metacognitive ability (Kipnis & Hofstein, 2008), scientific process skills (Deters, 2005), and attitude to science (Gibson & Chase, 2002).…”
Section: Inquiry-based Teachingmentioning
confidence: 99%
“…These result are in agreement with the previous observation that although inquiry-based approaches normally take more effort and time to develop, they are usually very positively perceived by students, who become more actively involved in their learning process and find this type of research experience very rewarding. [29][30][31] At a time when graduate employability is a key issue for higher education, as new graduates are faced with a highly competitive and rapidly evolving employment landscape, a shift from more traditional teaching systems to other thought-provoking learning approaches will help promote those skills and attributes that are most valued by employers. 22,32…”
Section: Students' Feedbackmentioning
confidence: 99%